Identity and Religion in Palestine The Struggle between Islamism and Secularism in the Occupied Territories - Lybarger, Loren D. 1964- (Princeton Studies in Muslim Politics, 2018)
This remarkable book examines how the Islamist movement and its competition with secular-nationalist factions have transformed the identities of ordinary Palestinians since the first Palestinian uprising, or intifada, of the late 1980s. Drawing upon his years living in the region and more than eighty in-depth interviews, Loren Lybarger offers a riveting account of how activists within a society divided by religion, politics, class, age, and region have forged new identities in response to shifting conditions of occupation, peace negotiations, and the fragmentation of Palestinian life. Lybarger personally witnessed the tragic days of the first intifada, the subsequent Oslo Peace Process and its failures, and the new escalation of violence with the second intifada in 2000. He rejects the simplistic notion that Palestinians inevitably fall into one of two camps: pragmatists who are willing to accept territorial compromise, and extremists who reject compromise in favor of armed struggle. Listening carefully to Palestinians themselves, he reveals that the conflicts evident among the Islamists and secular nationalists are mirrored by the internal struggles and divided loyalties of individual Palestinians. Identity and Religion in Palestine is the first book of its kind in English to capture so faithfully the rich diversity of voices from this troubled part of the world. Lybarger provides vital insights into the complex social dynamics through which Islamism has reshaped what it means to be Palestinian